Uncovering individual-level determinants of shared e-scooting travel frequency - Sajad Askari; Mahsa Merikhipour; Ehsan Rahimi; Farideddin Peiravian; Abolfazl (Kouros) Mohammadian (Multimodal Transportation, 2025)
Shared electric scooter services (SESS) can potentially contribute to sustainable urban transport. However, utilization rates remain low and cast doubt on their cost-effectiveness, energy and resource efficiency, and environmental benefits. While aggregate-level studies have examined shared e-scooter usage, individual-level factors remain underexplored. This study addresses that gap using a behavioral survey of 1,425 responses. We employed a random parameter ordered probit model to quantify the factors that influence the frequency of SESS usage. Study findings reveal a gender and generational gap, with women and older adults less likely to utilize e-scooter sharing compared to men, Millennials, and Gen Z. Additionally, low-income individuals and those without vehicles have a higher probability of being regular users. Multimodal transit users and individuals who receive reduced-fare transit are more likely to use SESS frequently. Individuals who shop online regularly, often a tech‑savvy group, are also more inclined to be frequent users. Furthermore, our findings indicate that built environment attributes are important. Specifically, the results show that living in areas with higher employment entropy, denser road networks, greater accessibility by transit, and highly walkable environments increases the likelihood of frequent SESS use.